Genetic Imbalance in Patients with Cervical Artery Dissection - Grond-Ginsbach, Caspar; Arnold, Marie-Luise; Kloss, Manja (Current genomics, 2017)
Background: Genetic and environmental risk factors are assumed to contribute to the susceptibility to cervical artery dissection (CeAD). To explore the role of genetic imbalance in the etiology of CeAD, copy number variants (CNVs) were identified in high-density microarrays samples from the multicenter CADISP (Cervical Artery Dissection and Ischemic Stroke Patients) study and from control subjects from the CADISP study and the German PopGen biobank. Microarray data from 833 CeAD patients and 2040 control subjects (565 subjects with ischemic stroke due to causes different from CeAD and 1475 disease-free individuals) were analyzed. Rare genic CNVs were equally frequent in CeAD-patients (16.4%; n=137) and in control subjects (17.0%; n=346) but differed with respect to their genetic content. Compared to control subjects, CNVs from CeAD patients were enriched for genes associated with muscle organ development and cell differentiation, which suggests a possible association with arterial development. CNVs affecting cardiovascular system development were more common in CeAD patients than in control subjects (p=0.003; odds ratio (OR) =2.5; 95% confidence interval (95% CI) =1.4-4.5) and more common in patients with a familial history of CeAD than in those with sporadic CeAD (p=0.036; OR=11.2; 95% CI=1.2-107)., Conclusion: The findings suggest that rare genetic imbalance affecting cardiovascular system development may contribute to the risk of CeAD. Validation of these findings in independent study populations is warranted.